2023
DOI: 10.1021/jacs.3c00774
|View full text |Cite
|
Sign up to set email alerts
|

Spiroborate-Linked Ionic Covalent Adaptable Networks with Rapid Reprocessability and Closed-Loop Recyclability

Abstract: Covalent adaptable networks (CANs) represent a novel class of polymeric materials crosslinked by dynamic covalent bonds. Since their first discovery, CANs have attracted great attention due to their high mechanical strength and stability like conventional thermosets under service conditions and easy reprocessability like thermoplastics under certain external stimuli. Here, we report the first example of ionic covalent adaptable networks (ICANs), a type of crosslinked ionomers, consisting of negatively charged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…This characterization showed that the tensile strength of HCIS-EP was comparable to that of conventional EP, and the strength remained high after five cycles of decrosslinking and crosslinking. Compared with the self-healing materials reported in other studies, 36–45 ISEP-RAP in this study had major advantages in terms of excitation conditions, mechanical properties, and healing (Fig. 8(b)).…”
Section: Resultsmentioning
confidence: 74%
“…This characterization showed that the tensile strength of HCIS-EP was comparable to that of conventional EP, and the strength remained high after five cycles of decrosslinking and crosslinking. Compared with the self-healing materials reported in other studies, 36–45 ISEP-RAP in this study had major advantages in terms of excitation conditions, mechanical properties, and healing (Fig. 8(b)).…”
Section: Resultsmentioning
confidence: 74%
“…When associative CANs are triggered, the cleavage and bonding occur simultaneously, and the cross-linking density remains constant, which are also coined “vitrimers” by Leibler and co-workers because of the silica-like rheological behavior . A variety of CANs have been reported via the introduction of DCBs, such as dynamic imine, , disulfide (selenide), Diels–Alder cycloaddition, transesterification, , thioester, silyl ether/siloxane, , boronic ester, reversible isocyanate chemistry, transamination, , transamidation, , transalkylation, nucleophilic aromatic substitution, and reversible conjugate addition. …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, thermoset composites with continuous fibers offer outstanding mechanical performance, thermal stability, and chemical resistance due to their crosslinked matrix materials. 21 The 3D printing methods for these composites can be categorized based on the chemical nature of the matrix resins, either thermally curable or UV-curable. For thermally curable composites, Fang et al 22 and Ming et al 23 demonstrated the 3D printing of epoxy composites with continuous carbon fiber.…”
Section: Introductionmentioning
confidence: 99%